2014
DOI: 10.1007/s11199-014-0418-0
|View full text |Cite
|
Sign up to set email alerts
|

Are You Man Enough to be a Nurse? The Impact of Ambivalent Sexism and Role Congruity on Perceptions of Men and Women in Nursing Advertisements

Abstract: Framed by role congruity and ambivalent sexism, the current study is designed to investigate perceptions of male and female nurses. Specifically, 167 Canadian undergraduates from Southern Ontario viewed a potential nursing recruitment advertisement (female nurse, male nurse, or masculinity emphasized male nurse), reported their perceptions of the nurse in the advertisement, and rated the appropriateness of nursing as a career for men and women. MANOVAs revealed that participants viewed the male nurses more neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 40 publications
2
45
0
1
Order By: Relevance
“…Men who enter the nursing profession get less support, are less valued, and often face more ridicule than do their female counterparts (Evans & Frank, ). Furthermore, people are particularly likely to perceive male nurses less favorably (e.g., as more deviant) than female nurses when the male nurses’ masculinity is emphasized (Clow, Ricciardelli, & Bartfay, ). Another study demonstrated that participants who were shown men in a stereotypically feminine setting, such as a kitchen, were quicker to categorize negative competence‐related than participants shown men in a stereotypically masculine setting, such as an office (de Lemus, Moya, Lupiáñez, & Bukowski, ).…”
Section: Factors Contributing To Adverse Reactionsmentioning
confidence: 99%
“…Men who enter the nursing profession get less support, are less valued, and often face more ridicule than do their female counterparts (Evans & Frank, ). Furthermore, people are particularly likely to perceive male nurses less favorably (e.g., as more deviant) than female nurses when the male nurses’ masculinity is emphasized (Clow, Ricciardelli, & Bartfay, ). Another study demonstrated that participants who were shown men in a stereotypically feminine setting, such as a kitchen, were quicker to categorize negative competence‐related than participants shown men in a stereotypically masculine setting, such as an office (de Lemus, Moya, Lupiáñez, & Bukowski, ).…”
Section: Factors Contributing To Adverse Reactionsmentioning
confidence: 99%
“…The same can be seen in studies about male nurses. Clow et al (2014) gives a good overview of perceptions of male nurses that are often negative. Several studies have also found that although most male nurses are heterosexual, the public perception is that male nurses are gay (e.g.…”
Section: My Point Of Viewmentioning
confidence: 99%
“…In this paper, Hardie (2015) also extends notions of female dominated occupations by considering them on a continuum, rather than dichotomously. Clow et al (2014) use role congruity theory and ambivalent sexism to examine reactions to advertisements for nursing school, exploring participants' reactions to portrayals of male nurses that include female, male, and overtly masculine images. This study also evaluates the likely success of attempts to recruit men into this profession by using and challenging stereotypes.…”
Section: The Present Issuementioning
confidence: 99%